The distribution of halogens (F, Cl, Br) in granitoid rocks - Teiber, Holger; Marks, Michael A. W.; Wenzel, Thomas; Siebel, Wolfgang; Altherr, Rainer; Markl, Gregor (Chemical geology, 2014)
The halogen contents of granitoid rocks and their distribution between apatite, biotite, muscovite and amphibole from two different localities (German part of the Bohemian Massif and Central Aegean, Greece) are investigated in detail. Whole rock F and Cl contents and F/Cl mass ratios vary systematically with the magmatic halogen-bearing mineral assemblage in which biotite and apatite are present in all rock samples: muscovite-bearing granites are F-rich (mostly 1100-2000μg/g, but up to 3100μg/g) and are relatively Cl-poor (50-130μg/g). In contrast, amphibole-bearing rocks reach high Cl contents (50-900μg/g) and are relatively F-poor (500-1400μg/g). Only biotite- and apatite-bearing granites show intermediate F (750-1100μg/g) and Cl (120-350μg/g) contents. Bromine contents of all rock samples are below the detection limit of about 0.6μg/g. In general, F and Cl are preferentially incorporated in apatite over biotite and biotite usually contains higher amounts of F and Cl than muscovite. Similarly, biotite prefers F over amphibole, but the distribution of Cl between biotite and amphibole varies between different rock samples. Bromine contents in muscovite are below the detection limit of 0.4μg/g, but can reach up to 0.8μg/g in biotite and up to 2.5μg/g in apatite and amphibole. Near-solidus effects such as fluid exsolution, diffusive re-equilibration and hydrothermal overprint may change the initial halogen distribution in the rock. Importantly, significant amounts of the whole rock's F (up to 60%) and Cl (up to 90%) may be accommodated in post-magmatic alteration phases (fluorite and Na-K-Ca-bearing sheet silicates) and fluid inclusions. Therefore, great care has to be taken when interpreting halogen contents of whole rocks and the influence of post-magmatic halogen-carriers needs to be taken into account.